Experimental estimation of sample entropy in a semiconductor laser with optical feedback for random number generation - Okuma, Tomohiko; Kanno, Kazutaka; Uchida, Atsushi (Frontiers in Complex Systems, 2024)
Estimating the entropy rate of physical random number generators with uncertainty is crucial for information security applications. We evaluate the sample entropy of chaotic temporal waveforms generated experimentally using a semiconductor laser with time-delayed optical feedback. We demonstrate random number generation with uncertainty using a quantitative measurement of the entropy rate.